2012
DOI: 10.1039/c2cp23869a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond effects in the ground and excited singlet states of 4H-1-benzopyrane-4-thione in water—theory and experiment

Abstract: The hydrogen bond energies for 4H-1-benzopyrane-4-thione (BPT) in its ground and two lowest excited singlet electronic states have been determined using ab initio methods. It was shown that the BPT molecule can form, as an acceptor, four relatively strong hydrogen bonds with water molecules, leading to a stable complex in the ground electronic state S(0). The hydrogen bonds involving the sulfur atom from the thiocarbonyl group were found to be stronger than those involving the oxygen atom from the benzopyran m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…It allows suggesting a possible mechanism for the change of their optical properties. Hydrogen bonds are known to affect the band gap of molecular complexes in both inorganic and organic nano‐assemblies . It was shown that interaction of a complex of the form A‐H–OH‐B can cause ionic and electronic rearrangement in both A and B upon excitation and can affect dramatically the bandgap as a function of the hydrogen bond strength.…”
Section: Resultsmentioning
confidence: 99%
“…It allows suggesting a possible mechanism for the change of their optical properties. Hydrogen bonds are known to affect the band gap of molecular complexes in both inorganic and organic nano‐assemblies . It was shown that interaction of a complex of the form A‐H–OH‐B can cause ionic and electronic rearrangement in both A and B upon excitation and can affect dramatically the bandgap as a function of the hydrogen bond strength.…”
Section: Resultsmentioning
confidence: 99%
“…We previously used similar way to determine energy of complexes formed between lumichrome (7,8‐dimethylalloxazine) and methanol or acetic acid . To calculate the hydrogen bond energy postulated in the ground and first excited singlet state, we used a model proposed by Krystkowiak and others for 4H‐1‐benzopyrane‐4‐thione (BPT) .…”
Section: Methodsmentioning
confidence: 96%
“…The procedure for independent and accurate determination of excitation or deactivation induced changes in the energy of nonspecific interactions and changes in the energy of particular types of hydrogen bonds proposed by us in [ 1 ] has been applied in this paper (as well as in [ 3 , 5 , 70 ]) for investigation of spectral and photophysical properties of 6AC and the complexes it makes with solvent molecules. The main aim of the study was to establish the effect of solute–solvent hydrogen bonds on the absorption and emission spectral properties and deactivation processes.…”
Section: Discussionmentioning
confidence: 99%